Thresholds of human body stability in water flows: advances, challenges, and guidelines for flood risk management - Marina Refatti Fagundes; Fernando Mainardi Fan; Gean Paulo Michel; Masato Kobiyama; Franciele Maria Vanelli; Leonardo Romero Monteiro; Karla Campagnolo; Jefferson Fagundes Loss; Bruno Henrique Abatti (Revista Brasileira de Recursos Hídricos)
ABSTRACT The occurrence of floods causes hundreds of drowning deaths annually. Therefore, it is necessary to develop measures and risk management policies related to flood disasters. One approach is the definition of stability thresholds for individuals in water flows, as safety is compromised when people are exposed to flows that surpass their ability to stand or cross. Based on these considerations, the objective of the study was to conduct a literature review of experimental, empirical, and theoretical studies on this topic, evaluating stability thresholds for individuals exposed to water flow. In total, 34 studies conducted until the year 2023 were identified. Key factors influencing stability include water flow characteristics and the physical attributes of individuals. In addition to these factors, adverse conditions such as uneven terrain, poor lighting, and psychological factors were also considered important. However, it was noted that few studies have assessed such adverse conditions, and there is a gap in the experimental analysis of these variables. Therefore, this study emphasizes the importance of conducting more physical experiments to address these gaps, obtain a more comprehensive database, and improve precision in numerical and experimental models, ultimately supporting tools for flood risk management.